1996
DOI: 10.1152/ajprenal.1996.270.5.f812
|View full text |Cite
|
Sign up to set email alerts
|

High glucose-induced TGF-beta 1 regulates mesangial production of heparan sulfate proteoglycan

Abstract: Previous investigations have demonstrated that growing mesangial cells in high glucose concentration stimulates extracellular matrix synthesis and also increases the expression of transforming growth factor-beta (TGF-beta). We examined the effects of hyperglycemia on mesangial proliferation and heparan sulfate proteoglycan (HSPG) and fibronectin production. Prolonged exposure of mesangial cells to increasing glucose concentrations resulted in dose-dependent effects on growth inhibition and stimulation of matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
55
0
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 0 publications
9
55
0
1
Order By: Relevance
“…High glucose concentrations increase TGF- . Further, increased glucose concentrations in vitro stimulate TGF-b mRNA expression and bioactivity, cellular hypertrophy and collagen transcription in proximal tubules [89] in addition to increased mesangial production of heparan sulphate proteoglycan [96].…”
Section: In Vitro Evidence For Tgf-b Effects On Kidney Cellsmentioning
confidence: 99%
“…High glucose concentrations increase TGF- . Further, increased glucose concentrations in vitro stimulate TGF-b mRNA expression and bioactivity, cellular hypertrophy and collagen transcription in proximal tubules [89] in addition to increased mesangial production of heparan sulphate proteoglycan [96].…”
Section: In Vitro Evidence For Tgf-b Effects On Kidney Cellsmentioning
confidence: 99%
“…The results of the Diabetes Control and Complications Trial have shown that strict prevention of hyperglycemia can prevent the onset and progression of diabetic nephropathy (4). In vivo and in vitro studies provide evidence that ambient high glucose induces the synthesis of extracellular matrix components (e.g., fibronectin) in glomerular and proximal tubular cells (5)(6)(7)(8)(9). There is ample evidence that the increased rate of glucose metabolism promotes the pathological changes in diabetic nephropathy (5,10).…”
mentioning
confidence: 99%
“…The hyperglycemia-induced TGF-␤ stimulates the production of fibronectin and other matrix proteins in mesangial and other renal cells (8,9,22). Activation of protein kinase C (PKC) isoforms (7,10,23), the hexosamine biosynthetic pathway (24,25), and the extracellular signalrelated kinase (ERK) 1 and 2 (26,27) and p38 mitogenactivated protein kinase (MAPK) pathway (28,29) have been implicated in the enhanced expression of TGF-␤1 and matrix proteins.…”
mentioning
confidence: 99%
“…3,4 The possible importance of TGF-␤1 in diabetic nephropathy has been demonstrated in vitro by glucose-induced upregulation of this cytokine in different cell types. [5][6][7][8][9][10][11][12][13] Increased TGF-␤1 expression has also been demonstrated in diabetic animal models and human patients. 14,15 TGF-␤ binds specific serine/threonine kinase type I and type II receptors.…”
mentioning
confidence: 99%